Main complications of hip arthroplasty: pictorial essay - Enge Júnior,Dair Jocely (2020)
Abstract Hip arthroplasty is a widely used and successful orthopedic procedure for the treatment of degenerative, inflammatory, or traumatic joint disease. The procedure promotes significant pain relief, as well as recovery of limb function, reduction of disability, and better quality of life. However, there are related complications, which have characteristic imaging aspects. In the present study, we review the literature and exemplify such complications using images obtained at our facility, illustrating the main radiological aspects of complications such as heterotopic ossification, periprosthetic fractures, osteolysis, infection, wear, and dislocation.